(untitled) (Research, Society and Development, 2020)
As a matter of instance, the purpose of this essay is to develop an analysis of the processes of teaching work as a condition for investments by International Agencies in many countries. Based on a series of regulations from such organizations (World Bank, IMF, OECD etc.), in Brazil’s precarious educational system, for example. As a result, postmodern pedagogies that aim to adapt the teaching process to the interests of these agencies are now being disseminated in Brazilian education. However, what is called “modern” and “quality” by ones, in educational terms, could be also considered as a process of precariousness by others. Deliberations that might scrap national education and deliver it to the interests of the international market also demean teaching work, which starts to be characterized as even more exploited and precarious.